Optimisation of sensor electrode size for in electrical resistance tomography implementing conducting boundary strategy - Suzanna, Ridzuan Aw; Ruzairi, Abdul Rahim; Fazlul Rahman, Mohd Yunus; Mohd Hafiz, Fazalul Rahiman; Yasmin, Abdul Wahab; Farah Hanan, Azimi; Lia Safiyah, Syafie; Nurul Huda, Mat Tahir; Raja Siti Nur Adiimah, Raja Aris; Shahrulnizahani, Mohammad Din (IOP Publishing, 2021)
Electrical Resistance Tomography (ERT), due to its diverse advantages has become a promising technique for monitoring and analysing various industrial flows. In this research, an ERT system employing a conducting bubble column was studied because a majority of industrial processes use metal composites for their columns. This paper presents an approach to obtain the optimum size of electrodes in ERT to maximize the capability of an ERT system. A finite element model using COMSOL software was developed to investigate the effect of the electrode size in ERT on sensing field distribution. By adapting the conducting boundary strategies in COMSOL, wider and longer electrodes reduce the potential change near source, suggesting less current density near source. Besides that, wider and longer electrodes also reduce the potential drop and improve the signal strength in Electrical Resistance Tomography. The optimum size of 12 mm x 100 mm electrode is sufficient for the proposed ERT system using conducting bubble column.